Emerging Roles and Potential Biological Value of CircRNA in Osteosarcoma - Liu, Jiamei; Yang, Liyu; Fu, Qin; Liu, Shengye (Frontiers in Oncology, 2020)
Circular RNAs (circRNAs) are endogenous non-coding RNAs that are widely found in eukaryotic cells. They have been found to play a vital biological role in the development of human diseases. At present, circRNAs have been involved in the pathogenesis, diagnosis and targeted treatment of multiple tumors. This article reviews the research progress of circRNAs in osteosarcoma (OSA) in recent years. The potential connection between circRNAs and OSA cell proliferation, apoptosis, metastasis, and chemotherapy sensitivity or resistance, as well as clinical values, are described in this review. Their categories and functions are generally summarized to facilitate a better understanding of OSA pathogenesis, and findings suggest novel circRNA based methods may be used to investigate OSA and provide an outlook for viable biomarkers and therapeutic targets.